Peningkatan PDRB Kota Padang Melalui Industri Pariwisata - Silfia Pattikawa (Jurnal Manajemen, Ekonomi, Keuangan dan Akuntansi, 2021)
Tourism is one of the mainstay sectors in Indonesia. There are so many areas that have tourism potential. And also the tourism sector is one of the sectors that the local government relies on, so the Padang city government of West Sumatra is required to be able to manage its tourism potential. This study aims to determine how the influence of tourism developing in Padang City to increase the city's economy. The purpose of this research was to determine the effect of the number of tourists visiting tourist attractions in Padang City on the PDRB. The research method that the writer does is with a quantitative approach because the data processing method used is writing based on the philosophy of positivism which is used to examine certain populations and samples. The results of this study are an increase in the PDRB of the city of Padang through the tourism industry.